This is the answer to the equation, but I do not understand why. Please help!
If you apply the Laws of Boolean Algebra one by one, the solution is a direct result:
OR
is the same as the complements of two terms joined by AND
, and vice versa (i.e. NOT(A + B) = NOT(A) * NOT(B)
and NOT(A * B) = NOT(A) + NOT(B)
).AND
or OR
is not important.AND
equals 0
respectively with OR
equals 1
(i.e. A * NOT(A) = 0
and A + NOT(A) = 1
).AND
with 0
equals 0
and joined with OR
with a 1
equals 1
(i.e. A * 0 = 0
and A + 1 = 1
).1
by AND
or with 0
by OR
is equal to itself (i.e. A * 1 = A
and A + 0 = A
).(there are more, but you don't need them here)
Applied to your term:
(A + NOT(B*C)) * (B + NOT(B*C)) * (C + NOT(B*C))
[with 1.] = (A + NOT(B) + NOT(C)) * (B + NOT(B) + NOT(C)) * (C + NOT(B) + NOT(C))
[with 2.] = (A + NOT(B) + NOT(C)) * (B + NOT(B) + NOT(C)) * (C + NOT(C) + NOT(B))
[with 3.] = (A + NOT(B) + NOT(C)) * (1 + NOT(C)) * (1 + NOT(B))
[with 4.] = (A + NOT(B) + NOT(C)) * 1 * 1
[with 5.] = (A + NOT(B) + NOT(C))
[with 1.] = (A + NOT(B*C))